2016
DOI: 10.4103/2231-0746.186128
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of mandibular ameloblastoma defect with the help of autologous dental pulp stem cells and buccal pad of fat stromal vascular fraction

Abstract: Ameloblastoma is benign odontogenic tumor, which is locally aggressive in behavior. Till date, the treatment of choice is resection and reconstruction using a variety of modalities. Inadequate resection may lead to many complications such as bone deformity and dysfunction. This report is about a 14-year-old male with ameloblastoma treated with autologous dental pulp stem cells (DPSCs) and stromal vascular fraction (SVF) and evidence of bone regeneration. Marsupialization was performed; tooth was extracted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Bone regeneration was confirmed through medical imaging. The authors observed no recurrence during the one and a half year follow-ups (Manimaran et al, 2016). Two patients suffering from medication-related osteonecrosis of the jaw (MRONJ) were treated with a combination of L-PRF and fresh SVF in a one-step procedure.…”
Section: Adipose Tissuementioning
confidence: 98%
See 2 more Smart Citations
“…Bone regeneration was confirmed through medical imaging. The authors observed no recurrence during the one and a half year follow-ups (Manimaran et al, 2016). Two patients suffering from medication-related osteonecrosis of the jaw (MRONJ) were treated with a combination of L-PRF and fresh SVF in a one-step procedure.…”
Section: Adipose Tissuementioning
confidence: 98%
“…Since then, MSCs have been studied in numerous clinical studies for representative diseases, including organ transplantation, diabetes, inflammatory, hematological, cardiovascular, autoimmune, cartilage, and bone disease (Squillaro et al, 2016). Clinical studies promoted non-union fracture healing (Hernigou et al, 2015), accelerated fracture healing (Kim et al, 2009) or bone regeneration in bone tissue defect (Pavan Kumar et al, 2016) and other pathological conditions (Manimaran et al, 2014(Manimaran et al, , 2016Bouland et al, 2020). The clinical applications of the different sources of MSCs are detailed in Table 1.…”
Section: Application Of Mscs In Bone Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…23 Moreover, hDPSCs demonstrated pro-angiogenic capability and are able to exert a positive effect in the regeneration of nerve tissue in vivo. 24 Daily, many live teeth are extracted for many reasons, such as avulsion and exfoliation or during orthodontics and periodontics.…”
mentioning
confidence: 99%
“…This method had an 84% success rate but does not work well with post radio-therapy patients or elderly people who have diminished bone precursor cells [30]. A combination of buccal fat pad stem cells (from the cheek) with iliac bone grafts has been used to treat maxillomandibular atrophy, and a resultant increased bone width was reported in the experimental group [30,31]. Similarly, allogenic chord stem cells or cranial derived bone marrow stem cells combined with alloplastic graft material for mandibular reconstruction has demonstrated some bone regeneration [22,23].…”
Section: Current Regenerative Therapies For the Jawmentioning
confidence: 99%